Combating Recession in Contemporary Times: Islamic Fiscal Policy and Nigeria’s Economic Recession - AbdulGafar Olawale FAHM; Ishaq Mustapha AKINLASO (IJUS | International Journal of Umranic Studies, 2022)
Recession is a major decline in fiscal activity spread across the economy, lasting more than a few months, normally visible in real GDP, real income, employment, industrial production, and wholesale-retail sales. Today, Nigeria is experiencing economic recessions because of a significant decline of Gross Domestic Product (GDP). Although the steady decline in goods and services is said to be steadily been reversed to normal, notwithstanding, people are taking the news of Nigeria’s economy steady exit from recession with a pinch of salt. This is because for a large portion of the population the costs of living still remain so oppressive. The study adopts historical, phenomenological, descriptive and remedial approach, leading to the fact that Nigeria as a nation can achieve economic success through Islamic fiscal policy in order to attain economic stability, growth, and an acceptable distribution of wealth which are embodied in Islamic teachings. The study, therefore, concludes that the Islamic fiscal policy can guide Nigerian government in its spending and taxation in order to positively influence the economy.